Electricity use as a real time indicator of the economic burden of the COVID-19-related lockdown: Evidence from Switzerland - Benedikt Janzen; Doina Radulescu (University of Bern, Department of Economics, 2020)
We employ hourly electricity load data for Switzerland as a real time indicator of the economic effects of the lockdown following the spread of SARS-CoV-2. Our findings reveal that following the drastic lockdown, overall electricity use decreased by 4 per cent, with a reduction of even 11.3 per cent in the Canton of Ticino where the number of confirmed cases per capita was one of the highest in Switzerland and also stricter measures such as closures of construction sites and industrial companies were implemented on top of federal regulations. Looking at working days only, we estimate a Swiss-wide decrease in electricity consumption of 6.3 per cent. Assuming industry, services, transport and agriculture account for 67 per cent of electricity demand, the 4 per cent decrease in electricity use implies a 6 per cent output reduction in these sectors. In addition, the reduced electricity imports and the change in the generation mix of neighbouring countries, also translates into reduced CO2 emissions related to these imports.
Keywords: C53; Q4; C3; 330; COVID-19; economic indicator; electricity load; CO2 emissions